Effect of Tiotropium on Cough Reflex Sensitivity in Acute Viral Cough - Dicpinigaitis, Peter V.; Spinner, Leah; Santhyadka, Ganesha; Negassa, Abdissa (Lung, 2008)
Study Objectives Cough is the most common complaint for which patients in the United States seek medical attention. Few, if any, effective therapies exist for the most common form of acute cough, that due to viral upper respiratory tract infection (URI). The aim of this study was to evaluate the effect of the anticholinergic agent tiotropium bromide on cough reflex sensitivity in subjects with acute viral URI. Patients Otherwise healthy adult nonsmokers with acute viral URI were randomized to receive inhaled tiotropium, 18 μg once daily, or matched placebo, for 7 days. A control group of healthy volunteers underwent an identical protocol. Measurements and Results Cough reflex sensitivity to inhaled capsaicin was measured at baseline (Day 0), and 1 h after the first (Day 1) and seventh (Day 7) dose of tiotropium or placebo. Concentrations of capsaicin inducing two or more ( C 2 ) and five or more coughs ( C 5 ) were determined. In subjects with URI, tiotropium ( n = 11) demonstrated inhibition of cough reflex sensitivity relative to baseline (increased log C 2 [ p = 0.004] and log C 5 [ p = 0.0004]) after the first dose. No change occurred in the placebo group ( n = 10). After 7 days, mean log C 2 was significantly increased in the tiotropium group relative to placebo ( p = 0.03). Although FEF 25–75 was also increased in the tiotropium group ( p = 0.016), there was no significant correlation between changes in cough reflex sensitivity and FEF 25–75 . Tiotropium had no effect in healthy volunteers ( n = 24). Conclusions Tiotropium inhibits cough reflex sensitivity to capsaicin in subjects with acute viral URI. The antitussive effect of tiotropium may occur through a mechanism other than bronchodilation.